DIGITAL GOLD IN INDONESIA: BRIDGING REGULATORY AND SHARIA GAPS - Afif Noor; Supangat; Aqila-Syarief Muhammad Afif; Muhammad Fazli Azmi (Jurnal Al-Dustur, 2026)
This study examines the development of digital gold in Indonesia by analyzing regulatory gaps and Sharia compliance. The primary objective of this study is to assess the extent to which the current regulatory system aligns with Islamic law standards and to address legal ambiguities that impact both market participants and Muslim consumers. This study employs a qualitative approach, utilizing normative legal analysis and a literature review of financial regulations and fiqh mu‘āmalah principles related to digital gold. Official documents, regulations issued by the Financial Services Authority (OJK), and fatwas issued by Islamic legal institutions serve as data sources. The current regulatory framework lacks adequate integration with Sharia, leading to inconsistent legal practices and unclear standards. This regulatory ambiguity is evident in the status of digital gold as a commodity or financial instrument. Furthermore, the lack of uniform standards regarding gold ownership by selling platforms, storage mechanisms, and transparency of physical gold reserves adds to the uncertainty. In the context of fiqh mu‘āmalah, this violates Sharia principles such as riba (usury), gharar (gharar), bai' al-ma'dum (risk of betting), and maisir (gambling). Without clear regulations, digital gold can be problematic from both legal and Sharia-compliant perspectives. The research demonstrates the necessity to merge positive law with Islamic legal values to establish a legally valid digital gold system that is transparent and Sharia-compliant. The study proposes that regulators, industry stakeholders, and the Sharia Supervisory Board should collaborate to establish standardized practices and regulations. The development of adaptive Sharia-compliant digital gold regulations represents a strategic approach to promoting safe and sustainable growth in digital investment in Indonesia. The findings of this study provide a strong academic foundation for examining the effectiveness of Sharia regulations and governance in digital investment products, highlighting the importance of this research in the development of Islamic finance and digital investment.